PENGARUH MODEL PREDICT-OBSERVE-EXPLAIN (POE) MELALUI METODE EKSPERIMEN TERHADAP KETERAMPILAN PROSES SAINS MAHASISWA PADA MATA KULIAH EKOLOGI HEWAN - Nurhidaya Fithriyah Nasution (Jurnal Education and Development, 2016)
This research was aimed to know the effect of Predict-Observe-Explain (POE) model by experiment method on science process skill of students in ecology of animal subject matter. The population in this research was all students in semester V STKIP Tapanuli Selatan which was consisted of two classes, they were class VA and class VB. The sample in this research was all students in semester V, they were class VA and class VB. The research type was quasi experiment using the totalling sampling method. The data obtaining used the instrument of science process skill. The data analysis used t-test, obtained tcount= 8.05 while ttable= 1.67 (in significant degree α = 0.05). This resut meant that tcount> ttable hence the H0 was refused and Ha was accepted. Therefore, there was the significant effect in using Predict-Observe-Explain (POE) by using experiment method on science process skill of students in ecology of animal subject matter.